Analisis Pengaruh Kebijakan Dividen, Struktur Modal, dan Struktur Kepemilikan Terhadap Kinerja Keuangan dengan Investasi Sebagai Variabel Intervening pada Industri Rokok yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2022 - Mayrilin Kayla Dedyanti; Hwihanus Hwihanus (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This research focuses on financial performance as a core element in evaluating a company's health and productivity, considering that it reflects the extent to which the company is able to manage resources, generate revenue, and meet its financial obligations. In a business context, financial performance not only reflects the results of various strategic decisions taken by management, but also becomes a benchmark for investors, creditors and other decision makers to measure the company's long-term growth and stability potential. The three main indicators for analyzing financial performance are Current Ratio (CR), Return on Assets (ROA), and Return on Equity (ROE). In this research, there are several variables that support the dependent variable (Y), namely financial performance. The supporting variables are Dividend Policy, Capital Structure, Ownership Structure, and Investment as Intervening variables. Quantitative research methods are used to analyze data from company financial reports on the Indonesian Stock Exchange. These factors, such as Dividend Policy, Capital Structure, and Ownership Structure, are expected to have a significant impact on the financial performance of cigarette companies. This research contributes to the literature by focusing on a less exposed sector, namely the cigarette sector, and introducing a better method of measuring financial performance.